AN ANALYSIS ON THE USES OF THE MEMORY CONCEPT IN BRAZILIAN INFORMATION SCIENCE - Bastos, Ana Wanessa Barroso; Nunes, Jefferson Veras [UNESP] (My University, 2023)
Its aim is to identify the most recurrent authors in citations on memory and their approaches in research related to the topic in the field of Information Science. In this sense, through a bibliographic survey, the citations of articles published in the Reference Database of Journal Articles in Information Science (BRAPCI) between 2017 and 2021 were analyzed, in order to identify the approaches most adopted in the area with regard to the study of memory, highlighting an informational, historical and cultural perspective, as well as a social one. From this, the interdisciplinary nature of the way the concept is understood was addressed, which led to the emergence of new paradigms in the area. The number of articles on memory has grown in the last five years when taking into account the same period prior to the one analyzed, confirming the growing frequency of the theme, contributing to the advancement of theoretical-conceptual discussions in the field of Information Science in Brazil, as well as with regard to professional practices.
UMA ANÁLISE SOBRE OS USOS DO CONCEITO DE MEMÓRIA NA CIÊNCIA DA INFORMAÇÃO BRASILEIRA
Keywords: Information Science in Brazil; Interdisciplinarity; Memory